PENGARUH PENGETAHUAN, SOSIALISASI, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Mutiara; Levi Martantina (Politeknik Ubaya, 2023)
This study aims to determine the relationship between Tax Knowledge owned by online store owners, socialization that has been obtained, and the sanctions that have been set affect compliance in paying final income tax. The population in this study are Kpop online store owners who sell physical and Kpop merchandise. This study uses one dependent variable represented by Taxpayer Compliance and three independent variables represented by Knowledge, Socialization, and Tax Sanctions. Data was obtained by distributing questionnaires, after which the data was calculated using statistical methods with the help of the Statistical Program For Social Science (SPSS).